Human T-lymphotropic virus 2 (HTLV-2) prevalence of blood donors in the state of Pará, Brazil - Correa, Lucas Pinheiro; da Costa Farias, Fatyene; dos Santos Barile, Katarine Antonia; Palmeira, Maurício Koury; de Melo Amaral, Carlos Eduardo (Brazilian journal of microbiology, 2023)
Introduction The present study had the objective to describe the molecular prevalence and epidemiological aspects of the human T-lymphotropic virus 2 (HTLV-2) infection in the blood donor population of the Pará state. Methods The present study is a descriptive, retrospective, and cross-sectional review of epidemiological, serological, and molecular data on inapt blood donors in the State Center for Hematology and Hemotherapy from January 2015 to December 2021. The data were digitalized to create a database using the Statistical Package for Social Sciences program. The prevalence of HTLV-2 was calculated based on the total number of donations during the study period. Descriptive frequency was used to analyze the qualitative data. Results A total of 665,568 blood donations were made. Out of these, 1884 (0.2%) samples presented serological detection to HTLV and further were evaluated using molecular confirmatory tests. Out of these, 36 samples were positive for HTLV-2 using qPCR Taqman assay based on pol gene region (0.005%). The HTLV-2 was found to be more prevalent in women (63.9%); aged between 39 and 59 years (55.6%); residents of the metropolitan region of Belém (80.6%); with self-declared race as brown (80.6%); individuals who had completed high school (58.6%); and first-time donors (58.3%) Conclusion The present study identified the presence of HTLV-2 (1 HTLV-2 case/20,000 donations; 0.005%) in the specific population of blood donors in Pará state. These findings can contribute to the existing literature on the subject both for specific population groups under study and for understanding the prevalence of HTLV-2 in the general population.